A strategic perspective on São Paulo’s high-end office market for foreign investments: the JLL’s case study - Maia, Caio Ricardo Vieira (2022)
The objective of this case study is to analyze and describe, by the lens of a real estate consultancy, why the Brazilian real estate market is attractive for foreign investors, analyzing their strategic view of this market and comparing this perspective with the perspective of a foreign investor that operates in Brazil. The focus of this study will be on São Paulo’s High-End Office and its foreign investors passing through previous findings, JLL’s perspective about this type of investment in this market to finally test JLL’s view doing a triangulation exercise with a foreign investor aiming to understand if JLL has a strategic view aligned with the actual foreign investors. To achieve this goal, this text is going to cover government incentives, socioeconomical factors, real estate market characteristics, foreign investments in other sectors, the coronavirus pandemic and other aspects that can interfere on the decision process of foreign investors and compare the importance given to these aspects by a foreign investor and the perceived importance seen by a multinational real estate consultancy. To fulfill this objective, this study will be based in a triangulation exercise of the documentation of JLL, archival records and an interview with Brookfield, the foreign investor with the highest amount of owned area in São Paulo. The findings of this paper will not only provide an analysis regarding the strategic view of a consultancy on this market but can also help the government and real estate companies of the São Paulo’s market in the key factors they should focus in order to attract more foreign investments to São Paulo’s High-End Real Estate Office Market.